(untitled) (Homoeopathy for All, 2021)
The trends of medical education are greatly changing with the introduction of advanced learning technologies and new educational approaches. The medical teachers have to play a wide range of key roles in the education process which extend far beyond imparting theoretical and stereotype concepts. They should be student-friendly, humble, easily approachable; enthusiastic, empathetic, humorous; good motivator, assessor and caretaker of personality development of the learners. If the medical teachers will possess these qualities and impart effective teaching, then it will pave the way to produce good quality doctors.